Clinical Outcomes of Donor Sites After Osteochondral Graft Harvest From Healthy Knees - Nakagawa, Yasuaki (Orthop J Sports Med, 2017)
BACKGROUND: The use of autologous osteochondral grafts has become popular in the treatment of small, isolated, well-contained articular cartilage defects. However, donor site morbidity is a problem, and few reports are available of donor site morbidity after mosaicplasty. PURPOSE: To examine the clinical outcomes of donor sites after osteochondral grafts from healthy knees. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: Between September 1997 and September 2011, there were 40 patients (40 knees; 32 men, 8 women; 31 right knees, 9 left knees) with asymptomatic osteochondral graft donor sites used for autologous transfer; all had a follow-up period of >2 years. The mean patient age at surgery was 21.0 years (range, 12-58 years). The recipient sites included the elbow (n = 28), contralateral knee (n = 5), and ankle (n = 7). The mean diameter of the grafted plugs was 7.5 mm (range, 4.5-9 mm), and the mean number of grafted plugs was 2.2 (range, 1-3). At a mean follow-up of 43.1 months (range, 24-177 months), knee symptoms, return to sport, ability to sit straight in Japanese style, and radiological changes of the patellofemoral joint were evaluated. Whether operative age, follow-up period, and diameter or number of the grafted plugs were risk factors was analyzed statistically. Significance was defined as P < .05. RESULTS: Thirty-four patients had no knee symptoms, and 4 patients had occasional mild knee pain. Two patients underwent reoperation for arthrofibrosis and not for cartilage defect. Twenty-seven patients had complete return to sports, and 32 patients could sit straight; donor site morbidity was not the cause of failure to return to sports or inability to sit straight. The radiological changes became worse in 3 patients, and the risk factor for degenerative change was older operative age. CONCLUSION: When osteochondral plugs were obtained from healthy knees, 34 patients (85%) were asymptomatic at follow-up. No donor site defects required surgical intervention due to persistent symptoms.